Ø³Ø± Ø¨ØµÙ…Ø© Ø§Ù„Ø¨Ù†Ø§Ù† ÙÙŠ Ø§Ù„Ù‚Ø±Ø¢Ù†: Ø¯Ø±Ø§Ø³Ø© ØªØÙ„ÙŠÙ„ÙŠØ© ÙÙŠ Ø³ÙˆØ±Ø© Ø§Ù„Ù‚ÙŠØ§Ù…Ø©: Ù£-Ù¤ - Isna Lutfia Agustina (UIN Siber Syekh Nurjati Cirebon, 2019)
Humans are the most perfect creatures of Allah Swt. Every human has different fingerprints. Even for two people who are identical twins, they have the characteristics of fingerprints that are not the same. Therefore, fingerprints are used in identity cards that are very important for their owners and are used throughout the world. Previously, people valued fingerprints as ordinary arches without special meaning. But in the Qur'an, Allah gave references to fingerprints, which did not attract people's attention at that time, and direct attention to the importance of fingerprints, which can only be understood today. The method used in this study is literature review using content analysis techniques and the data sources in this study are books, thoughts, and writings related to the research object. The results of this study show that the Qur'an has stated that fingerprints are human identification. In the Qur'an, it is mentioned that it is easy for Allah to revive a human being after his death, which is specifically mentioned in the Qur'an, Surah al Qiyamah verses 3-4.